Increase of Brivaracetam serum concentration with introduction of Cenobamate - Bender, Lena; Hirsch, Martin; Schulze-Bonhage, Andreas (Frontiers in Pharmacology, 2025)
IntroductionCenobamate is a new antiseizure medication approved for polytherapy of focal epilepsy with complex hepatic metabolism and effects on liver enzymes. So far, data are limited with regard to possible interactions with other antiseizure medications. We here report effects of Cenobamate on serum levels of Brivaracetam, a SV2-agent modulating presynaptic neurotransmitter release.MethodsRetrospective analysis of Brivaracetam serum concentrations with new introduction of Cenobamate with Brivaracetam as a constant baseline antiseizure medication in 19 patients with focal epilepsy. Statistical analysis using paired Fisher´s exact t-Test.ResultsNew introduction of Cenobamate lead to a statistically significant increase in Brivaracetam serum concentrations with a mean increase by 27%. This was infrequently accompanied by adverse effects.DiscussionNew introduction of Cenobamate to a pre-existing antiseizure regimen containing Brivaracetam leads to considerably increases in Brivaracetam, probably related to inhibition of CYP2C19. This needs to be taken into account when interpreting changes in treatment efficacy, but also when relating potential adverse effects to baseline vs. newly introduced treatment.